Periodic domino game: a possibility for teaching and learning one of the periodic table (Research, Society and Development, 2020)
Studies and research show that chemistry Teaching is, in most cases, traditional, centered only on the memorization of names and formulas; with this, it distances itself from the reality of the student, becoming difficult and annoying. One of the chemistry contents that raise the most doubts in the students is the periodic table, most of them cannot assimilate the properties and the way the elements were organized. As an alternative to reduce these difficulties arise the games, didactic-pedagogical tools help the teacher in an attractive and dynamic way. In this sense, the present work should aim to verify the acceptance and the influence in the application of the game Domino Periodic in the classes on the periodic table. For that, field research was carried out with 19 students of the 9th grade of Elementary School II of the Centro Educacional Espaço Criativo School, in the municipality of Quiterianópolis-CE. The data were collected through an evaluative questionnaire, and the results graphically presented showing that the game aroused the interest of the students, since 64% of them attributed a maximum score and had an excellent influence, since 95% of the students stated that the game contributes significantly to a better understanding of the content addressed.